Isolation Of Shigatoxigenic Escherichia Coli From Faeces And Farm Water Samples Of Sheep Using Pcr - CH. BINDU KIRANMAYI; N. KRISHNAIAH; N. SUBHASHINI; MANI MAHESWARI (International Journal of Pharma and Bio Sciences, 2011)
Apart from cattle, sheep and goat are important natural reservoirs of Shigatoxigenic Escherichia coli. Faecal contamination during dressing of carcass accounts for the presence of STEC in raw meat. A total of 201 samples (104 sheep faecal and 97 sheep farm water samples) collected from various sources were subjected to PCR analysis for the presence of Shigatoxigenic Escherichia coli using primers specific to STEC virulent genes, shiga toxins (stx1 and stx2) and enterohaemolysin (hlyA) with amplification size of 614bp, 779bp and 361bp respectively. Out of 201 samples, 93 showed presence of STEC (36 faecal and 27 water samples). Of the 93 STEC positive isolates, 63 (67.74%) showed presence of stx1, 32 (34.4%) showed stx2, 47 (50.53%) showed hlyA gene and 16 (17.2%) showed both stx1 and stx2. Among 58 STEC positive isolates, 7.52% (4 faecal and 3 water samples) isolates possessed all the 3 virulent genes. Enrichment with modified Tryptic Soy Broth (mTSB) containing novobiocin gave good results compared to modified Escherichia coli (mEC) broth with novobiocin.